Povidone-iodine vs chlorhexidine alcohol for skin preparation in malignant and premalignant gynaecologic diseases: A randomized controlled study. (January 2020) - Gezer, Sener; Yalvaç, Hayriye M.; Güngör, Kübra; Yücesoy, İzzet
Abstract: Objectives: To compare povidone-iodine with chlorhexidine alcohol solutions for the prevention of surgical site infection (SSI) in malignant and premalignant gynaecologic diseases, and to evaluate the effects of temperature on SSI at 25 °C and 37 °C. Study design: This was a randomized controlled trial of a cohort of 220 patients undergoing surgery for malignant or premalignant conditions. Preoperative skin preparations were performed with 10% povidone-iodine at 25 °C (PI), 10% povidone-iodine at 37 °C (warm PI), 4% chlorhexidine gluconate with alcohol at 25 °C (CH) and 4% chlorhexidine gluconate with alcohol at 37 °C (warm CH) for each group. All women included in the study received 1 g intravenous cefazolin antibioprophylaxis 30 min before skin incision. The primary outcome was SSI within 30 days of surgery, and secondary outcomes were identification of the causative organism and clinical factors that may be associated with SSI. Results: SSIs were detected in 24 (10.9%) patients. Except for two organ/space-specific SSIs, all were superficial SSIs. The frequency of SSI was significantly lower in the warm PI group than in the PI group ( p = 0.032). There were no significant differences in the frequency of SSI between the groups in other binary comparisons. In addition, there was no significant difference between both povidone-iodine groups compared with both chlorhexidine alcohol groups in terms of the development of SSI (10.9% vs 11%, p = 1.00). SSI caused by micro-organisms was found in 18 patients, and Enterococcus faecalis was the most common reproducing organism in wound culture. Patients with SSI were significantly older (58.9 ± 11.4 vs 52.8 ± 12.3 years) and more likely to be readmitted to hospital [15 (62.5%) vs 9 (37.5%)] than patients without SSI. Conclusions: SSI rates can be reduced by warming povidone-iodine, but this effect could not be demonstrated with chlorhexidine solutions. When both groups of povidone-iodine were compared with both groups of chlorhexidine alcohol, no significant difference was found in the prevention of SSI in malignant and premalignant gynaecologic operations.